2019
DOI: 10.3390/ani9121153
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Licorice Root Feeding on Chemical-Nutritional Quality of Cow Milk and Stracciata Cheese, an Italian Traditional Fresh Dairy Product

Abstract: The aim of this study was to evaluate the effect of dietary licorice root supplementation on chemical and nutritional characteristics of cow milk and Stracciata cheese. Licorice did not influence milk and Stracciata fat content but induced modifications in fatty acid profile. Both in milk and Stracciata, a decrease in saturated fatty acids was detected and in cheeses an increase of monounsaturated and polyunsaturated fatty acids was observed. Stracciata obtained from the experimental group showed an improved o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…The role of volatile flavor compounds in meat has been widely investigated [37,38], and several studies paid attention to the possibility to induce variations in volatile profile of animal products by changing the feeding strategies [39], especially through the exploitation of vegetable matrices rich in biologically active compounds [10,40,41].…”
Section: Discussionmentioning
confidence: 99%
“…The role of volatile flavor compounds in meat has been widely investigated [37,38], and several studies paid attention to the possibility to induce variations in volatile profile of animal products by changing the feeding strategies [39], especially through the exploitation of vegetable matrices rich in biologically active compounds [10,40,41].…”
Section: Discussionmentioning
confidence: 99%
“…It has been widely observed that the diet administered to lactating ruminants is commonly responsible for changes in the volatile profile of dairy products, both fresh and ripened [165,166]. It is, therefore, conceivable that compounds present in the diet, or secondary metabolites of the same, can be absorbed by the animal following digestion and then reach the mammary gland and be released into the milk [167].…”
Section: Ruminantsmentioning
confidence: 99%
“…It has been widely observed that the diet administered to lactating ruminants is commonly responsible for changes in the volatile profile of dairy products, both fresh and ripened [113][114][115][116]. It is, therefore, conceivable that compounds present in the diet, or secondary metabolites of the same, can be absorbed by the animal following digestion and then reach the mammary gland and be released into the milk.…”
Section: Volatile Flavor Compounds and Sensorial Evaluationsmentioning
confidence: 99%